2017
DOI: 10.1016/j.bbr.2017.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of social and novelty enrichment on individual differences in impulsivity and behavioral flexibility

Abstract: Early life experience profoundly impacts behavior and cognitive functions in rats. The present study investigated how the presence of conspecifics and/or novel objects, could independently influence individual differences in impulsivity and behavioral flexibility. Twenty-four rats were reared in an isolated condition, an isolated condition with a novel object, a pair-housed social condition, or a pair-housed social condition with a novel object. The rats were then tested on an impulsive choice task, a behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
1
17
0
Order By: Relevance
“…A potential caveat of the SP-5-CSRTT is that rats were housed individually in CombiCages. Social isolation in rats can lead to increased stress levels and altered neuroendocrine state, particularly during early weaning (Serra et al 2000; Weiss et al 2004; Weintraub et al 2010), which has been found to impact executive functions in rats (Kirkpatrick et al 2013; Wang et al 2017). Notably, these effects are most pronounced when social isolation occurs following early weaning, for instance starting at postnatal day 21.…”
Section: Discussionmentioning
confidence: 99%
“…A potential caveat of the SP-5-CSRTT is that rats were housed individually in CombiCages. Social isolation in rats can lead to increased stress levels and altered neuroendocrine state, particularly during early weaning (Serra et al 2000; Weiss et al 2004; Weintraub et al 2010), which has been found to impact executive functions in rats (Kirkpatrick et al 2013; Wang et al 2017). Notably, these effects are most pronounced when social isolation occurs following early weaning, for instance starting at postnatal day 21.…”
Section: Discussionmentioning
confidence: 99%
“…impulsive choice delay task followed by the time discrimination task or impulsive choice magnitude task followed by the reward magnitude discrimination task). Between the impulsive choice and the discrimination tasks, a buffer task was administered to reduce side biases and carry-over effects (Wang, Marshall, & Kirkpatrick, 2017). After the first set of impulsive choice and discrimination tasks, the rats completed another buffer task and the lever assignments were switched before beginning the next set of impulsive choice and discrimination tasks to minimize carryover effects.…”
Section: Methodsmentioning
confidence: 99%
“…Buffer task.-A modification of the lever press training was used in between each task to minimize side biases and the carryover effects from one task to another. Wang et al (2017) found that the buffer task minimized cross-task interference and eliminated side biases. The first session delivered FR1 → RR3 → RR5 schedules from lever press training where each schedule was trained for one block with 20 reinforcers earned on each lever, constituting three blocks in total.…”
Section: 33mentioning
confidence: 97%
“…Finally, the effects of social versus the non-social (novelty, exercise, etc.) components of enrichment are also dissociable by several measures including brain weight that is more responsive to environment complexity than social conditions (Rosenzweig et al, 1978), and differential effects on impulsivity, behavioral flexibility, and memory (Prado Lima et al, 2018;Wang et al, 2017).…”
Section: Genes and Environment: Towards A Model For Effects On Bementioning
confidence: 99%